Electronic medical records sharing solution based on Hyperledger Fabric - CHEN Jiali; MA Ziqiang; MIAO Li; LI Bingyu; YUE Xiaolin (Tongxin xuebao)
In addressing the issues of medical record ownership and access control during the storage and sharing processes of electronic medical record (EMR), an EMR sharing solution based on Hyperledger Fabric was put forward . In this solution, EMR was encrypted and stored in IPFS (inter planetary file system) using proxy re-encryption technology implemented through smart contracts, depending on the conditions for sharing. The IPFS addresses of the records were recorded on the blockchain to ensure their immutability. For sharing EMR, patients established strict access control policies. Through the use of CP-ABE (attribute-based encryption) and the Asmuth-Bloom secret sharing algorithm, the EMR was encrypted so that only authorized personnel can access them. Simultaneously, parties involved in secret sharing collaborate to recover keys and decrypt the records.The document comprehensively discusses the security aspects of this solution, ensuring that EMR can withstand various attacks during storage and sharing, thus guaranteeing data integrity and privacy. Compared to other secret sharing schemes, this solution demonstrates better theoretical time complexity, providing an efficient and reliable solution for secure storage and multi-party sharing of EMR.